A differentially selective probe for trivalent chemosensor upon single excitation with cell imaging application: potential applications in combinatorial logic circuit and memory devices. Issue 1 (21st November 2018) - Das, Dipankar; Alam, Rabiul; Katarkar, Atul; Ali, Mahammad
Abstract : A new rhodamine 6G-benzylamine-based sensor (L 1 ) shows selective recognition of trivalent metal ions with advanced level molecular logic gate and bio-imaging applications. Abstract : A new rhodamine 6G-benzylamine-based sensor (L 1 ), having only hydrocarbon skeletons in the extended part, was synthesized and characterized by single-crystal X-ray crystallographic study. It exhibited excellent selective and sensitive recognition of trivalent metal ions M 3+ (M = Fe, Al and Cr) over mono- and di-valent and other trivalent metal ions. A large enhancement of the fluorescence intensity for Fe 3+ (41-fold), Al 3+ (31-fold) and Cr 3+ (26-fold) was observed upon the addition of 3.0 equivalent of these metal ions into the probe in H2 O/CH3 CN (4 : 1, v/v, pH 7.2) with naked eye detection. The corresponding K f values were evaluated to be 9.4 × 10 3 M −1 (Fe 3+ ), 1.34 × 10 4 M −1 (Al 3+ ) and 8.7 × 10 3 M −1 (Cr 3+ ). Quantum yields of theL 1, [L 1 –Fe 3+ ], [L 1 –Al 3+ ] and [L 1 –Cr 3+ ] complexes in H2 O/CH3 CN (4 : 1, v/v, pH 7.2) were found to be 0.012, 0.489, 0.376 and 0.310, respectively, using rhodamine-6G as standard. LODs for Fe 3+, Al 3+ and Cr 3+ were determined by 3σ methods and found to be 1.28, 1.34 and 2.28 μM, respectively. Cyanide ion scavenged Fe 3+ from the [Fe 3+ –L 1 ] complex and quenched its fluorescence via its ring-closed spirolactam form. Advanced level molecular logic devices using different inputs (2 and 4 inputs) as advanced level logic gates and memory devices were constructed. The large enhancement in fluorescence emission ofL 1 upon complexation with M 3+ metal ions makes the probe suitable for the bio-imaging of M 3+ (M = Fe, Al and Cr) in living cells.